Waste reduction and bioconversion of quail, chicken, and pig manure by Black Soldier Fly (Hermetia illucens) - Diola, Clayton Sprewel T. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Methods to reduce wastes and convert them into usable products are urgently needed as wastes from food production are expected to increase with human population. In this study, I assessed the effectiveness of black soldier fly (Hermetia illucens) larvae (BSFL) in reducing animal waste and converting it into frass. The BSFL were reared on three different waste streams (quail, chicken, and pig manure) for six days and the waste reduction index (WRI), bioconversion rate (BR), and frass characteristics were measured and compared across manure types and with those measured on quail manure applied with effective microorganisms (EMO) only. Based on the WRI and overall degradation of dry matter, the BSFL reduced the quail, chicken, and pig manure by 62.49 ± 1.94 %, 25.83 ± 1.24 %, and 24.70 ± 1.32 % overall degradation of dry matter, respectively while the application of EMO did not reduce the waste (-15.18 ± 0.47 %). This demonstrates that the BSFL is effective in reducing the three different wastes examined. With the same amount of substrate fed to the larvae, the BSFL fed with quail manure can convert more ingested waste to biomass (BR = 26.41 ± 0.68 %) compared to the larvae fed with chicken and pig manure (BR = 9.11 ± 0.51 % and 17.98 ± 0.28 %, respectively). The frass produced had no odor and had a sand like texture while the by-product from EMO composting produced foul manure-like odor and black viscous fluid, indicating that the BSFL converted the animal manure into potentially usable by-products. Organic matter content (17.05 - 29.20 %) and NPK content of the frass were high but pH values ranged from 8.13 ± 0.02 to 8.85 ± 0.02, which is above the pH range (5.5 - 6.5) ideal for plant growth. Lastly, the BSFL reared on quail, chicken, and pig manure was high in protein (10.10 - 12.10 %) and low in fat content (1.66 - 2.93 %). In conclusion, the results of this study reveal the potential of BSF larvae in reducing waste and converting them to frass and protein rich biomass.